Analisis Penggunaan Platform Digital sebagai Informasi Lokasi Destinasi Wisata: Tinjauan Literatur Sistematis - Cynthia Widya Lestari; Arista Pratama; Asif Faroqi (Universitas Multi Data Palembang, 2026)
Digital platforms have become a primary source of location-based information for tourism destinations and play a significant role in shaping tourists’ decision-making processes. This study aims to identify research trends, types of digital platforms, theoretical models, and key variables influencing the use of destination location information through a Systematic Literature Review (SLR). The literature search was conducted using Scopus, ScienceDirect, Sinta, and Google Scholar, covering articles published between 2021 and 2025, with 20 studies meeting the inclusion and quality assessment criteria. The findings indicate that social media and travel applications are the most dominant digital platforms used. Theoretical model frequently applied include UTAUT2, TAM, TPB, and hybrid models, with UTAUT2 emerging as the most comprehensive framework for explaining user behavior. Significant influencing variables include performance expectancy, effort expectancy, social influence, hedonic motivation, habit, facilitating conditions, and perceived trust, while price value tends to have a limited effect. This study systematically maps theoretical models, variables, and empirical findings related to the use of destination location information on digital platforms, providing a structured conceptual foundation for future research on tourist behavior.